Interfacial colloidal self-assembly for functional materials - Hou, Shuai (2023)
Conspectus: Self-assembly bridges nanoscale and microscale colloidal particles into macroscale functional materials. In particular, self-assembly processes occurring at the liquid/liquid or solid/liquid/air interfaces hold great promise in constructing large-scale two- or three-dimensional (2D or 3D) architectures. Interaction of colloidal particles in the assemblies leads to emergent collective properties not found in individual building blocks, offering a much larger parameter space to tune the material properties. Interfacial self-assembly methods are rapid, cost-effective, scalable, and compatible with existing fabrication technologies, thus promoting widespread interest in a broad range of research fields. Surface chemistry of nanoparticles plays a predominant role in driving the self-assembly of nanoparticles at water/oil interfaces. Amphiphilic nanoparticles coated with mixed polymer brushes or mussel-inspired polydopamine were demonstrated to self-assemble into closely packed thin films, enabling diverse applications from electrochemical sensors and catalysis to surface-enhanced optical properties. Interfacial assemblies of amphiphilic gold nanoparticles were integrated with graphene paper to obtain flexible electrodes in a modular approach. The robust, biocompatible electrodes with exceptional electrocatalytic activities showed excellent sensitivity and reproducibility in biosensing. Recyclable catalysts were prepared by transferring monolayer assemblies of polydopamine-coated nanocatalysts to both hydrophilic and hydrophobic substrates. The immobilized catalysts were easily recovered and recycled without loss of catalytic activity. Plasmonic nanoparticles were self-assembled into a plasmonic substrate for surface-enhanced Raman scattering, metal-enhanced fluorescence, and modulated fluorescence resonance energy transfer (FRET). Strong Raman enhancement was accomplished by rationally directing the Raman probes to the electromagnetic hotspots. Optimal enhancement of fluorescence and FRET was realized by precisely controlling the spacing between the metal surface and the fluorophores and tuning the surface plasmon resonance wavelength of the self-assembled substrate to match the optical properties of the fluorescent dye. At liquid/solid interfaces, infiltration-assisted (IFAST) colloidal self-assembly introduces liquid infiltration in the substrate as a new factor to control the degree of order of the colloidal assemblies. The strong infiltration flow leads to the formation of amorphous colloidal arrays that display noniridescent structural colors. This method is compatible with a broad range of colloidal particle inks, and any solid substrate that is permeable to dispersing liquids but particle-excluding is suitable for IFAST colloidal assembly. Therefore, the IFAST technology offers rapid, scalable fabrication of structural color patterns of diverse colloidal particles with full-spectrum coverage and unprecedented flexibility. Metal-organic framework particles with either spherical or polyhedral morphology were used as ink particles in the Mayer rod coating on wettability patterned photopapers, leading to amorphous photonic structures with vapor-responsive colors. Anticounterfeiting labels have also been developed based on the complex optical features encoded in the photonic structures. Interfacial colloidal self-assembly at the water/oil interface and IFAST assembly at the solid/liquid/air interface have proven to be versatile fabrication platforms to produce functional materials with well-defined properties for diverse applications. These platform technologies are promising in the manufacturing of value-added functional materials.